Human Resource Management and Organizational Commitment of Commercial Banks in Nawalpur - Lamsal, Bishnu Prasad (Madhyabindu Journal, 2023)
Human resource management (HRM) is the practice of recruiting, hiring, deploying and managing an organization’s employees. Organizational performance is the ability of an organization to reach its goals and optimize results. The aim of this study is to explore the perception of employees regarding HRM practices, the relationship between HRM practices and employee satisfaction. The study also aimed to find out the relationship between HRM practices and organizational commitment in Nepalese commercial banks in Nawalpur. The study was based on the quantitative research design and the participants in this study were the bank’s employees’ human resource management and their performance. The sample size for this study was maintained at 150 participants. To evaluate the phenomenon of the survey, a closed questionnaire was formulated. The results of this study indicated that recruitment and selection practices and organizational commitment are effective in Nepalese commercial banks. But training and development practice, compensation practice and performance appraisal practice is not so effective in Nepalese commercial banks.